Association of GR GENE Polymorphism with T2DM among North Indian Population - Syed Tasleem Raza, Kisa Saiyeda, Shania Abbas (International Journal of Scientific Research and Management (IJSRM), 2017)
Background & Objective: Diabetes mellitus is a complex metabolic disorder and is escalating at a very fast rate across the globe in 21st century and is a pressing problem for the world and especially for our nation. Genetics has given us a solution to most of the unsolved mysteries and therefore it was very rational to investigate the association of GRL gene polymorphism with T2DM among north Indians. Methods: A total of 50 blood samples in each group of T2DM cases and of healthy controls were collected randomly from Diabetes clinic in Medicine Department of ELMC&H. Genomic DNA was isolated from whole blood using the standard phenol-chloroform extraction method. The DNA concentration was determined by spectrophotometer and stored at -20°C. Ethical committee’s clearance was obtained from Institutional Ethics Committee, prior to the commencement of the study. Results: Frequencies of GRL GG, GT and TT genotypes in T2DM cases and controls were 2%, 24%, 74% and 0%, 8%, 92% of GRL G and T allele was 4%, 96% in cases and 14%, 86% in the controls respectively. Odd Ratio of GT was 3.63(95% CI=1.08-12.18, X2=4.76, p values=0.029), for GG NA (95% CI=NA, X2=1.01, p values=0.315) and for TT 0.25 (95% CI=0.07-0.82, X2=5.74, p values=0.017). Interpretation & Conclusion: On the basis of the findings of this study it is concluded that GRL GT and TT genotype is significantly (p=0.029, 0.017) associated with T2DM. The short study period, small sample size and financial restrains were the limitations of the study. There is need to carry out a multicentric study on larger sample size and for a longer duration to find out a genetic solution of the escalating problem of T2DM.